Changes in arsenic exposure in Araihazar, Bangladesh from 2001 through 2015 following a blanket well testing and education campaign. (April 2019) - Huhmann, Brittany L.; Harvey, Charles F.; Navas-Acien, Ana; Graziano, Joseph; Parvez, Faruque; Chen, Yu; Argos, Maria; Ahmed, Alauddin; Hasan, A.K.M. Rabiul; Ahsan, Habibul; van Geen, Alexander
Abstract: Background: Concentrations of arsenic (As) are elevated in a large proportion of wells in Bangladesh but are spatially variable even within a village. This heterogeneity can enable exposed households to switch to a nearby well lower in As in response to blanket (area-wide) well As testing. Objectives: We document the evolution of As exposure in Araihazar, Bangladesh following a blanket well testing and education campaign, as well as the installation of a considerable number of low As community wells. Methods: We use well water and urinary As data collected between 2000 and 2008, along with household interviews extending through 2016, within a 25 km 2 area of Araihazar upazila for nearly 12, 000 participants enrolled in the Health Effects of Arsenic Longitudinal Study (HEALS). We observe changes in participants' well water and urinary As concentrations following interventions to lower their exposure and use logistic regression to determine the factors associated with participants' decisions to switch primary household wells. Results: Urinary As for participants drinking from wells with >100 μg/L As at baseline declined from a mean of 226 μg/L at baseline to 173 μg/L two years later, and further declined to 139 μg/L over 8 years. For comparison, urinary As concentrations for participants drinking from wells with ≤10 μg/L As remained close to 50 μg/L throughout. Whereas the interventions only partially reduced exposure, well status with respect to As was predictive of well-switching decisions for at least a decade after the initial testing. Participants with high-As wells were 7 times more likely to switch wells over the first two years and 1.4–1.8 times more likely to switch wells over the ensuing decade. Conclusions: Arsenic exposure gradually declined following blanket well testing, an education campaign, and the installation of community wells but remained almost three times higher than for a subgroup of the participants drinking from wells with ≤10 μg/L. In addition, the number of participants with unknown As concentrations in their primary household wells increased substantially over time, indicating the importance of additional well testing as new wells continue to be installed, in addition to other means of reducing As exposure. Highlights: Well and urine As data collected for 8 years from 12, 000 villagers in Bangladesh. Urine As for villagers with >100 μg/L well As declined from 226 to 139 μg/L over 8 years. Urine As for villagers with ≤10 μg/L well As remained close to 50 μg/L throughout. Number of participants with unknown well As increased substantially over time.